The Relationship between Compressive Strength and Pore Structure of the High Water Grouting Material - Youmin Han; Junwu Xia; Linli Yu; Qiong Su; Xiaomiao Chen (Crystals, 2021)
To elucidate the relationship between compressive strength and pore structure of the high water grouting material with different water-binder ratios and CaO contents, the compressive strength was tested while pore structure including pore characteristic parameters and pore diameter distribution were investigated by BET, MIP, and 3D-XRM. Moreover, the evolution of hydration products was observed by TGA and SEM, illustrating the reactive mechanism of the material. Furthermore, the grey correlation coefficients between compressive strength and pore structure parameters were illustrated according to the grey correlation theory. The results show that CaO content in lime is proportional to the compressive strength with the water-binder ratio of 1.0 or 1.5, while the inverse trend appears with the water-binder ratio of 2.0. The high water grouting material belongs to the macropore material with the pores mainly within 100 nm to 2 μm. Its hydration products contain ettringite crystals, aluminum gels, and C-S-H gels. The productions of the hydration products are positively correlated with its compressive strength. In addition, the compressive strength of the high water grouting material is closely related to the pore characteristic parameters and the pore size distribution, especially the porosity, the most probable pore diameter, and the pore volumes within 100~500 nm and 10~100 nm.